Historicist and Presentist Interpretation of Shakespeare’s Twelfth Night - Sharif Mohammad Shahidullah (University of Chitral Journal of Linguistics and Literature, 2019)
Historicism and Presentism are two recent, mostly discussed phenomena in theethos of Shakespearean studies. While historicists like Stephen Greenblatt arguesthat historicism pursues historical aspects to explain a text and keeps away presentdaypolitical, social and cultural affairs to avoid the misunderstanding of it, thepresentists like Terence Hawkes advocates that Presentism offers an unendingdialogue between present and past, which is deeply rooted to the present. Inaddition, Presentism is the re-evaluation of the historical facts upon which our earlymodern understanding depends. Therefore, Presentism could be an excellent ideato interpret the appropriacy of early modern literature, especially Shakespeare’soeuvre. This paper, however, elucidates Twelfth Night, one of Shakespeare’smasterpieces, from both historicist and presentist points of view, which looksespecially at the way Shakespeare views gender while applying these bothapproaches. This article also clarifies the reasons for selecting this text forexplicating Shakespeare from these two approaches. Finally, this study advocatesfor combining these two approaches, which might offer a better way to understandShakespeare’s works and to make him more relevant today.